The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.macromol.8b00335
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Nanoparticle Dynamics in Poly(N-isopropylacrylamide) Gels

Abstract: Nanoparticle (NP) probes were used to characterize the local structure of N-isopropyl­acrylamide (NIPAAM), a thermoresponsive hydrogel, using single particle tracking (SPT). Swelling ratio, and thus gel network confinement, was varied by tuning polymer and cross-linker concentrations. Based on the swelling ratio, the volume phase transition (VPTT) was determined to be near 32 °C. In general, NPs were found to be localized by two barriers. A primary localization region of approximately 100 nm was attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 43 publications
(105 reference statements)
4
32
0
Order By: Relevance
“…Average mesh size, ξ, is calculated for each polymer network and the dynamics of a tracer particle is compared as a function of ξ/σ tr . Although several factors influence the dynamics of a tracer particle in polymer networks, such as interactions between a tracer particle and polymer segments [8,19,33], aggregation of polymer segments of the network [30], and network heterogeneity [19,31,32], we solely focus on the size-dependent obstructive effect of small meshes by investigating the diffusion of an inert, nonsticky tracer particle in homogeneous polymer networks. Similar with those in polymer solutions and melts [24,34,35], the dynamics of a tracer particle in polymer networks can be distinguished by the relative mesh size to that of a tracer particle, ξ/σ tr [36].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Average mesh size, ξ, is calculated for each polymer network and the dynamics of a tracer particle is compared as a function of ξ/σ tr . Although several factors influence the dynamics of a tracer particle in polymer networks, such as interactions between a tracer particle and polymer segments [8,19,33], aggregation of polymer segments of the network [30], and network heterogeneity [19,31,32], we solely focus on the size-dependent obstructive effect of small meshes by investigating the diffusion of an inert, nonsticky tracer particle in homogeneous polymer networks. Similar with those in polymer solutions and melts [24,34,35], the dynamics of a tracer particle in polymer networks can be distinguished by the relative mesh size to that of a tracer particle, ξ/σ tr [36].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of tracer diffusion provides important pieces of microscopic information on the structural and dynamic properties of underlying polymeric materials, including polymer films [ 5 , 6 , 7 , 8 , 9 , 10 ], and biological cells [ 11 , 12 , 13 , 14 , 15 ], and on the penetration and mobility of analytes in polymer gels employed in a broad range of applications for drug delivery and sensors [ 9 , 16 , 17 ]. Among polymer networks, stimuli-responsive hydrogels serve as an interesting platform for the study of tracer diffusion [ 7 , 8 , 9 , 18 , 19 ], because the internal structure of the polymer networks can be altered significantly upon changes in environmental conditions, such as temperature, pH, ionic strength, and solvent quality [ 20 , 21 , 22 ]. However, the dynamics of molecules and nanoparticles in hydrogels is not well understood at the nanoscopic and mesoscopic scales, particularly with respect to the effect of change in the internal structure of the polymer network on molecular transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, fundamental research on ionic polymer nanocomposites to understand and investigate the ionic interactions, nanoparticle mobility on the interphasial region, and nanoparticle dispersion state of the nanocomposite have not been performed so far. Exceptions are the coarse grained model by Hong et al [79,80] for nanoparticle ionic liquids, where nanoparticles diffuse like in a polymer solution [81,82,83] while chains diffuse faster than nanoparticles, as well as the studies in ionomer nanocomposites [59,84], polymer charged solutions [85,86] and polymer gels [87,88].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been reported on the diffusion of NPs entrapped in thermoresponsive hydrogels and there are no effective models for predicting the mobility of NPs in a polymeric network with thermally induced phase transitions. Because of a lack of effective mathematical or physical models, many experimental efforts have been made to determine the diffusion of NPs using single particle tracking (SPT) [37][38][39] or measuring the uptake and release of drugs into thermo-sensitive hydrogels [40,41]. However, in these works, experimental characterization can be laborious and expensive, or only a few factors were considered.…”
Section: Introductionmentioning
confidence: 99%